Effect of thread dimensions of functionally graded dental implants on stress distribution - Celik, Nevin; Kaman, Mete Onur (Elsevier Sci Ltd, 2013)
[Abstract Not Available]
European Biotechnology Congress -- MAY 16-18, 2013 -- Comenius Univ, Bratislava, SLOVAKIA